The Aesthetics Of Poetic Discourse In Abu-alkasim Saadallah’s The Green Time: A Study Of The Poem "the Return Of The Eagles - Souaker Brahim (University of El oued, 2025)
his paper aims to study the poetic discourse of "The Return of the Eagles", one of the poems from Saadallah’s collection "The Green Time". It traces the aesthetic elements of the discourse and links them to the overarching meaning of the poem, thathe composed during the Algerian War of Independence to commemorate the return of emigrants to their homeland. The study seeks to address the central question: What are the key characteristics of the aesthetic elements in the poem’s poetic discourse, and what are its most significant interpretations? The findings reveal that thecollectionas a whole, and the selected poem in particular, represent a rich and profound poetic text that encapsulates a pivotal moment in the revolution. It also reflects the experiences of this encyclopedic young man who lived through the colonial period and the Algerian Revolution.
Article .El-Quari'e Journal of Literary, Critical and Linguistic Studies
Keywords: Discourse; Poetry; Revolution; The Green Time; The Return Of The Eagles